POTENTIAL AND BENEFITS OF ECOENZYMES : A LITERATURE REVIEW FOR SUSTAINABLE ENVIRONMENTAL MANAGEMENT - Qurratu Aini; Nurul Fajriana; Suwarniati Suwarniati; Achmad Zacky (Jurnal Biologi Sains dan Kependidikan, 2024)
Ecoenzyme is an organic fermentation solution obtained from household organic waste, which has great potential in supporting sustainable environmental management. This study aims to review the benefits and applications of ecoenzymes based on current literature, and evaluate their relevance to global environmental challenges. The results of the review indicate that ecoenzymes play an effective role in waste treatment, pollution reduction, and improving soil and water quality. In addition, ecoenzymes also contribute to climate change mitigation by reducing greenhouse gas emissions. Despite its significant benefits, the adoption of ecoenzymes on a large scale faces challenges, such as the lack of standardization of production processes and the need for more in-depth scientific validation. Therefore, further research is needed to optimize the use of ecoenzymes and support their application in various sectors. This study is expected to be a reference for the development of environmentally friendly technologies that are in line with the principles of sustainable development. Key words: ecoenzyme, environmental management, sustainable development, climate change mitigation, organic waste